The Conception and Classification of Thinnings - Singh, Partap (Indian Forester, 1947)
In making a thinning in a crop, foresters seldam agree. They rely on instinct (or experience or the so-called knowledge of the silvicultural requlrements of the crop) as little more is understood about thinning beyond the fact that it consists in the removal of some of the worst trees in the crop. The theory of dominance of trees and the commoner mode of diagrammatic representation has added confusion to the paucity of knowledge. In this paper, the present position has been examined, the nature of thinnings and their regimes, as related to the laws of growth studied, relationship between crop dimension and differenciations stated, the basis of a relevant tree classification evolved thinning order list revised, and natural grades of thinnings enuncfated. The basic foundations of all the ralationas and empirical methods of thinnings have been analysed and correlated and a few other important questions relating to thinnings explained. The genesis of this very briefly written paper is the freedom of the crown as opposed to the prevalent universal ideas about dominance in tree crops.